Treasure and spiritual exile in Old English "Juliana": Heroic diction and allegory of reading in Cynewulf’s art of adaptation - Olesiejko, Jacek (Adam Mickiewicz University, 2013)
The present article studies Cynewulf’s creative manipulation of heroic style in his hagiographic poem Juliana written around the 9th century A.D. The four poems now attributed to Cynewulf, on the strength of his runic autographs appended to each, Christ II, Elene, The Fates of the Apostles, and Juliana are written in the Anglo-Saxon tradition of heroic alliterative verse that Anglo- Saxons had inherited from their continental Germanic ancestors. In Juliana, the theme of treasure and exile reinforces the allegorical structure of Cynewulf’s poetic creation. In such poems like Beowulf and Seafarer treasure signifies the stability of bonds between people and tribes. The exchange of treasure and ritualistic treasure-giving confirms bonds between kings and their subjects. In Juliana, however, treasure is identified with heathen culture and idolatry. The traditional imagery of treasure, so central to Old English poetic lore, is inverted in the poem, as wealth and gold embody vice and corruption. The rejection of treasure and renunciation of kinship bonds indicate piety and chastity. Also, while in other Old English secular poems exile is cast in terms of deprivation of human company and material values, in Juliana the possession of and preoccupation with treasure indicates spiritual exile and damnation. This article argues that the inverted representations of treasure and exile in the poem lend additional strength to its allegorical elements and sharpen the contrast between secular world and Juliana, who is an allegorical representation of the Church.
Keywords: Cynewulf; Juliana; St. Juliana of Nicomedia; Old English poetry; Middle Ages